Response analysis of undamped primary system subjected to base excitation with a dynamic vibration absorber integrated with a piezoelectric stack energy harvester - Linh, N. N.; Tuan, V. A.; Tuan, N. V.; Anh, N. D. (Vietnam Journal of Mechanics, 2022)
Dynamic vibration absorber (DVA) integrated with a piezoelectric stack energy harvesting subjected to base excitation is introduced in this paper. The system of dynamic vibration absorber and piezoelectric stack energy harvesting system (DVA-PSEH) has two functions, the first is to reduce vibrations for the primary system, and the second is to convert a part of the vibrational energy into electricity through the piezoelectric effect. The mechanical and electrical responses of the electromechanical system are determined by the complex amplitude method, then the numerical simulations are carried out to investigate the characteristics of DVA-PSEH.